(untitled) (Journal of Lithic Studies, 2016)
This research represents a first approach to the characterization of blade fractures produced intentionally using various techniques, according to an experimental protocol. The objective is to establish a reference base of marks which serve to define the fractures documented in the archaeological record. The fractured blade being a very common element in different sites throughout in the Iberian Peninsula during the Neolithic and Chalcolithic Ages. In fact, from the Late Neolithic a new concept applied to the creation of lithic tools arose, involving the fracturing of blades through the improvement of fracturing techniques. In addition, a preference for obtaining the mesial fragments of the blades or those which have more regular measurements can be observed. This type of lithic instrument represents high percentages of all the retouched material, and may possess only one fractured end or, more commonly, both, bi-fractured. With the archaeological evidence, we decided to carry out an experiment to define and classify the marks that result during the intentional fracturing of laminar fragments, contemplating different variables. We used three types of techniques for fracturing blades: flex, direct percussion and indirect percussion, and we used different types of hammer, made of stone, antler and copper. For the results, we have standardized the descriptions of different parts of the fracture distinguishing: types of fracture, fracture planes, fracture marks and macrowear. However, we should point out that this experimentation is the beginning of a line of research that, over time, must integrate a wider experimental base which also considers the other mentioned causes of fracture, as well as the functional objective of these tools. The preliminary study through this experimentation has made it possible to define and describe the types of fractures resulting from the use of different blade fracturing methods. We also have described the main types of fracture marks generated from each fracturing technique.